Comparison Between Media Literacy and Information Literacy in Textbooks of Public in High School and Civics in Junior High School - FUJISAKI, Seiya (Japan Journal of Educational Technology, 2023)
We compare the usage of “media literacy” and “information literacy” from descriptions in the textbooks of “public”, a compulsory subject in high school, and of “civics” in social studies of junior high school. As a result, the difference between the literacy is in “public” more ambiguous than in “civics”. In addition, while “criticism” and “judgment” are important in media literacy, description in textbooks of “public” requires that high school students should act more concretely and proactively than in junior high school. Textbooks of “civics” include more references to mass media than of “public”, suggesting that high school students need to pay more attention to the Internet, such as SNS. In addition, it is necessary to keep in mind the unique context of social studies, which seeks the awareness of the ”citizens” who shape “public opinion”.